AL-MUSYTARAK AL-LAFDHI FI KALIMATI “JA’ALA” FI AL-QUR’AN AL-KARIEM (DIRASAH TAHLILIYAH DILALIYAH) - Oktapiani, Devi; Nurohman, Nurohman; Nugraha, Rahmat Mulya (Jazirah: Jurnal Peradaban dan Kebudayaan, 2021)
Dilalah is knowledge that has been studied for a long time. Part of Dilalah's is Musytarok Lafdzi. In the Qur'an there are many forms of words, including verbs, nouns or symbols, each form of this word has a complex meaning that requires knowledge that can support understanding the meaning correctly. The science that is used to understand the various types of words is called the Science of Dilalah or Semantics. In the Science of Dilalah there are many language speakers including ta'adudul ma'na or one word that has many meanings, synonyms, antonyms and many more. So the author uses the Dilalah Science principle as the basis for his research on the word Ja'ala in the Qur'an because it has many meanings in that one word. the purpose of this research is to find out the meaning of Ja'ala and its musytarok in the Qur'an, as well as the types of musytarok that exist in Ja'ala in the Al Qu'an.This research is a type of qualitative research, in which the author collects data sourced from books related to the discussion and opinions of linguists. Some of the sources used by the author in his research are books on semantics, we interpret them to find the meaning of lafadz Jaa'la in the Qur'an, an Arabic dictionary. One of the results of this study is that there are several meanings similar to the Ja'ala in the Qur'an, namely saddu, farroqo, soyyaro, yasiro, a'tho, ‎tsabata, ittakhoda and syaro'a. And the types of musytarok included in this lafadz include two musytarok mutlaq and seven musytarok haqiqi, and in this study the authors did not find any type of musytarok tadod.